Plasmodium falciparum: Assessment of Selectivity of Action of Chloroquine, Alchornea cordifolia, Ficus polita, and Other Drugs by a Tetrazolium-Based Colorimetric Assay. (1st December 2011) - Ayisi, Nana Kofi; Appiah-Opong, Regina; Gyan, Ben; Bugyei, Kwasi; Ekuban, Fred
Abstract : A tetrazolium-based colorimetric selective assay (MTT-based CSA) was developed to assess the selectivity of antimalarial drugs. This in vitro assay, unlike all others, measures the ability of drugs to indirectly protect red blood cells (RBCs) from Plasmodium-falciparum -induced destruction. Optimum incubation time and number of cells needed were 5 days and 23 × 10 6 RBCs per well, respectively. A parasitemia range of 0.375% to 3% was found to be suitable for this assay. The MTT-based CSA determined anti- P . falciparum strain DD2 activity of chloroquine at a higher 50% effective concentration (EC50 ) value (21.0 μ g/mL) than the isotopic microtest (10.0 μ g/mL). Artesunate and oxytetracycline achieved 90% effect against DD2 with minimal or no toxicity to RBCs. Against chloroquine sensitive strain 3D7, chloroquine and Alchornea cordifolia had EC50 values of 0.025 μ g/mL and 4.9 μ g/mL respectively, and selective index (SI) values of >2, 000 and >69.4 μ g/mL, respectively.